Laju Pertumbuhan dan Tingkat Kelangsungan Hidup Karang Jenis Acropora formosa dan Acropora intermedia Menggunakan Metode Transplantasi Modul Rangka Spider di Perairan Pantai Lipah, Desa Bunutan Kabupaten Karangasem, Bali - Pettalolo, Basyaasyah Rahmaningrum; Wiyanto, Dwi Budi; Dirgayusa, I Gusti Ngurah Putra (Journal of Marine Research and Technology, 2024)
Lipah Beach holds the potential for coral reefs, although this potential is considered moderate due to anthropogenic destructive activities. The spider skeleton method has been employed as a coral rehabilitation effort at Lipah Beach. Aside from its cost-effectiveness, the spider framework also provides a waterway. The success of coral rehabilitation can be measured by assessing the growth rate and survival rate of transplanted corals. Corals of the Acropora genus, including A. formosa and A. intermedia, are known for their rapid growth and high resilience. These corals possess significant aesthetic value but are currently threatened as they continue to be traded. The primary objective of this research is to determine the growth rate and survival rate of transplanted A. formosa and A.intermedia using the spider skeleton method. The research adopts an experimental approach with direct observation. Each type of coral, A. formosa and A. intermedia, is represented by 20 fragments, totaling 40 transplanted fragments. The study spans over 4 months to monitor coral growth and survival rates, along with monthly measurements of seawater quality parameters to assess their conditions. The findings reveal that A. intermedia exhibits a growth rate of 0.81 cm per month, surpassing that of A. formosa, which measures 0.73 cm per month. Conversely, the survival rate of A. formosa is higher at 75% compared to A. intermedia at 70%. By the end of the study, 15 fragments of A.formosa and 14 fragments of A. intermedia remained viable.